18 Years of Experience in Knee Arthroscopy Under Local Anesthesia. Issue 1 (1996) - Birkner, W.; Henche, H. R.
Abstract : Today, arthroscopies of the knee joint have become a routine procedure. Generally, these operations are performed under general or spinal anesthesia. In Rheinfelden, local anesthesia is our method of choice. We will summarize our experience with nearly 9000 arthroscopies in the last 18 years. We use 10 mls of ScandicainR as the local anesthetic for the puncture track, followed by an intraarticular injection of 20 mls of CarbostesinR. From 1977 to 1994, arthroscopies were performed on 8720 patients, of which 90% were outpatients, under local anesthesia. When asked about pain sensation, 50% of patients had no pain at all, 34% expressed mild pain and only 3% reported strong pain. 90% of all patients questioned responded that they would undergo the same procedure a second time, if necessary. There are several advantages of local anesthesia, most important the minimal invasive procedure. Risk factors can be avoided, the pain level described by the patients is acceptable and the costs are lower than with other anesthetizing techniques. As a prerequisite for performing these operations under local anesthesia, the surgeon must be very experienced in the handling and routine of arthroscopic procedures.